Regulation of the rabbit's once-daily pattern of nursing: a circadian or hourglass-dependent process?. (2nd August 2020) - Apel, Sabine; Hudson, Robyn; Coleman, Grahame J.; Rödel, Heiko G.; Kennedy, Gerard A.
ABSTRACT: The European rabbit Oryctolagus cuniculus has an unusual pattern of nursing behavior. After giving birth in a nursery burrow (or laboratory nest box), the mother immediately leaves the young and only returns to nurse for a few minutes once approximately every 24 h. It has been assumed this schedule, like a variety of other functions in the rabbit, is under circadian control. This assumption has been largely based on findings from mothers only permitted restricted access to their young once every 24 h. However, in nature and in the laboratory, mothers with free access to young show nursing visits with a periodicity shorter than 24 h, that does not correspond to other behavioral and physiological rhythms entrained to the prevailing 24 h light/dark (LD) cycle. To investigate how this unusual, apparently non-circadian pattern might be regulated, we conducted two experiments using female Dutch-belted rabbits housed individually in cages designed to automatically register feeding activity and nest box visits. In Experiment 1 we recorded the behavior of 17 mothers with free access to their young under five different LD cycles with long photo and short scotoperiods, spanning the limits of entrainment of the rabbit's circadian system. Whereas feeding rhythms were entrained by LD cycles within the rabbit's circadian range of entrainment, nursing visits showed a consistently shorter periodicity regardless of the LD regimen, largely independent of the circadian system. In Experiment 2 we tested further 12 mothers under more conventional LD 16:8 cycles but "trained" by having access to the nest box restricted to 1 h at the same time each day for the first 7 d of nursing. Mothers were then allowed free access either when their young were left in the box ( n = 6), or when the litter had been permanently removed ( n = 6). Mothers with pups still present returned to nurse them on the following days according to a similarly advancing pattern to the mothers of Experiment 1 despite the previous 7 d of "training" to an experimentally enforced 24 h nursing schedule as commonly used in previous studies of rabbit maternal behavior. Mothers whose pups had been removed entered the box repeatedly several times on the first day of unrestricted access, but on subsequent days did so only rarely, and at times of day apparently unrelated to the previously scheduled access. We conclude that the pattern of the rabbit's once-daily nursing visits has a periodicity largely independent of the circadian system, and that this is reset at each nursing. When nursing fails to occur nest box visits cease abruptly, with mothers making few or no subsequent visits. Together, these findings suggest that the rabbit's once-daily pattern of nursing is regulated by an hourglass-type process with a period less than 24 h that is reset at each nursing, rather than by a circadian oscillator. Such a mechanism might be particularly adaptive for rhythms of short duration that should end abruptly with a sudden change in context such as death or weaning of the young.